2012
DOI: 10.1590/s0080-62342012000300029
|View full text |Cite
|
Sign up to set email alerts
|

A formação acadêmica de enfermagem e os incidentes com múltiplas vítimas: revisão integrativa

Abstract: O estudo objetiva refletir acerca dos saberes, competências e habilidades que devem ser fomentados durante a formação acadêmica de enfermagem para uma atuação profissional eficaz perante um incidente com múltiplas vítimas (IMV). Trata-se de uma revisão integrativa da literatura acerca da formação dos acadêmicos de enfermagem. O levantamento bibliográfico foi efetuado nas bases de dados BDENF, LILACS, SciELO, MEDLINE, Web of Knowledge e HighWire Press, utilizando os descritores: educação superior; educa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
8

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 19 publications
0
13
0
8
Order By: Relevance
“…Initial care to burn victims: nursing students' knowledge -a cross-sectional study Online braz j nurs [internet] 2014 Sep [cited year month day]; 13(4):518-28. Available from: http://www.objnursing.uff.br/index.php/ nursing/article/view/4744 critical situations, including providing services to burn patients at trauma centers (10) . Thus, the team in charge should base their assistance on established scientific principles, and the nurses are the ones responsible for carrying out the treatment of the most complex cases (8) .…”
Section: Introductionmentioning
confidence: 99%
“…Initial care to burn victims: nursing students' knowledge -a cross-sectional study Online braz j nurs [internet] 2014 Sep [cited year month day]; 13(4):518-28. Available from: http://www.objnursing.uff.br/index.php/ nursing/article/view/4744 critical situations, including providing services to burn patients at trauma centers (10) . Thus, the team in charge should base their assistance on established scientific principles, and the nurses are the ones responsible for carrying out the treatment of the most complex cases (8) .…”
Section: Introductionmentioning
confidence: 99%
“…12 In some countries, such as Brazil, the law supports the nurses' performances on the critically ill patient and allows the execution of activities of greater technical complexity and which require a scientifically based knowledge and ability to make immediate decisions. 13 In the United States, a study conducted by nurses from the Massachusetts General Hospital (Boston, Massachusetts USA) concluded that the role of nursing in disaster medicine and LTEs will continue to grow in years to come, hence, the importance of nurses being adequately trained in this field. 14 Boyd 15 states that urgent care must correspond to a comprehensive emergency system as a set of sequential activities complex and ordered through protocols aimed at optimizing the care of critical patients from the moment of appearance of the process to their reincorporation to life social or labor.…”
Section: Discussionmentioning
confidence: 99%
“…13 Além disso, com as mudanças no cenário nacional, percebe-se a importância de serem inseridas novas temáticas no processo de ensino em U/E, relacionadas à epidemiologia dos incidentes com múltiplas vítimas (IMV) no cenário contemporâneo, somados aos desastres naturais, com consequências significativas para o SUS. 18 De modo geral, detecta-se a necessidade de mais aproximação dos serviços no processo de formação inicial do enfermeiro, ou seja, da diminuição da distância entre a teoria e a prática; nesse sentido, é de grande importância que se dê uma roupagem prática ao conteúdo, principalmente nessa perspectiva de formação por competência. Há autores, ainda, que defendem uma formação com predomínio de aulas práticas no serviço, ou seja, tomando os serviços como um dos determinantes dos conteúdos e competências a serem trabalhados.…”
Section: Conteúdos Das Aulas Pr áTicas No Serviço: Dependência Da Demunclassified